Whey Protein-Pectin Conjugate by Wet-Dry Heating: Optimization using Response Surface Methodology with Box-Behnken Design - Elita Yeliani; Arima Diah Setiowati; Chusnul Hidayat (agriTECH, 2023)
The recent progress in glycation of proteins utilizing saccharides through the Maillard reaction has garnered substantial attention, with a specific emphasis on Whey Protein Concentrate (WPC). Conjugation mode is frequently intricate and poses challenges when scaling up for large-scale production. Consequently, this investigation sought to optimize the conditions of the WPC-pectin conjugation process using Response Surface Methodology (RSM) in conjunction with Box-Behnken design (BBD). The experimentation was executed employing a cabinet dryer, incorporating both wet and dry heating procedures to yield a WPC-pectin conjugate exhibiting favorable functional properties. The independent variables investigated encompassed pectin concentration (ranging from 0 to 1%), pH (ranging from 6 to 8), and drying time (ranging from 2 to 6 hours), The measured responses encompassed the emulsion stability index (ESI), emulsifying activity index (EAI), and solubility. Analyzing the experimental data underwent scrutiny for model sufficiency through diagnostic plots, and a second-order polynomial equation was fitted through multi-response regression analysis, resulting in a high coefficient of determination (R 2 ) value. The most effective parameters were identified as a pectin concentration of 0.49%, pH 6.7, and a drying duration of 4.12 hours, yielding a peak ESI of 452.267 minutes, EAI measuring 49.95 m 2 g -1 , and solubility reaching 48.09%. Further experiments were conducted to validate these outcomes, and the presence of the Maillard reaction was confirmed using Fourier Transform Infrared Spectrum (FTIR). The et-dry method demonstrated efficacy in producing WPCpectin conjugates with commendable functional properties.